Influence Of Working Conditions In Garment Production On The Psychoemo-tional State And Central Nervous System Of Working Women - Slavinskaya N.V; Nuraliev F.N. (Journal of Advanced Zoology, 2023)
Research has established that during their work, seamstresses and motorists are exposed to the adverse effects of noise, general low-frequency vibration, increased air temperature, insufficient and uneven lighting, and the intensity of the labor process. From the beginning to the end of the working day, they experience a deterioration in their psycho-emotional state and the development of inhibitory processes in the central nervous system. It has been established that the noise level is characterized by an average degree of influence on worsening mood (r-0.42), decreased activity (r-0.47) and a high degree of influence on worsening well-being (r-1.0). The level of illumination is characterized by a high degree of influence on the deterioration of well-being (r-0.98) and does not affect activity (r-0.2) and mood (r-0.25). Correlation analysis of the dynamics of changes in indicators of the central nervous system showed a high degree of dependence on noise (r-0.89), illumination (r-0.99) and air temperature (r-0.99). To stabilize the indicators of the psycho-emotional state and the central nervous system of seamstresses and motorists, it is necessary to introduce measures to improve working conditions.